Financial performance of securities firms in Vietnam: The significance of business size and diversification - Nguyen, Dinh Hoan; Nguyen, Minh Duc; Nguyen, Thu Ha; Tran, Thu Thanh (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of business diversification and firm size on the financial performance of securities companies in Vietnam. Using secondary data from 33 publicly listed securities firms between 2010 and 2024, the research analyzes the effects of different business lines—proprietary trading, brokerage, consulting, and lending—on financial outcomes through quantitative methods. The findings reveal that both firm size and diversification have a significant impact on performance, with positive effects observed for business, consulting, and brokerage activities. In contrast, lending activities are associated with negative results. These outcomes confirm that diversification benefits securities firms in Vietnam, although the effects vary across different activities. The study contributes to the existing literature by providing empirical evidence over 14 years and highlights that strategic diversification can enhance or hinder financial success depending on the operational focus. Practical implications suggest that securities firms and Vietnamese authorities can leverage these insights to optimize diversification strategies and better prepare for Vietnam’s emerging stock market landscape, supporting sustained growth and development.